Comorbidities, medications and depressive symptoms in patients with restless legs syndrome and migraine Comorbidades, medicações e sintomas depressivos em pacientes com síndrome das pernas inquietas e enxaqueca - Karen S. Ferreira; Alan Eckeli; Fabíola Dach; José G. Speciali (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The pathophysiology of migraine and restless legs syndrome (RLS) seems to involve inherited mechanism and dysfunction of the dopaminergic system. Previous articles have shown that the frequency of RLS is higher in migraine patients than in controls. We conducted a study to evaluate comorbidities, medication used and depressive symptoms that can explain the relation between migraine and RLS. METHODS: A case-control study was performed in which patients with migraine (n=72) and a control group without migraine (n=72) were interviewed. Data including RLS diagnosis, depressive symptoms, comorbidities and drugs used were evaluated. RESULTS: There was a significant association between migraine and RLS (p=0.01), but comorbidities such as diabetes, hypertension, anemia and drugs used did not explain this association. Depression scores, as measured by the Beck Depression Inventory, were higher in migraine patients with RLS (p =0.04). CONCLUSION: No specific factors explaining the association between migraine and RLS were found. Symptoms of depression were more frequent in patients with migraine and RLS. OBJETIVO: A fisiopatologia da enxaqueca e da síndrome das pernas inquietas (SPI) parece envolver mecanismos genéticos e disfunção do sistema dopaminérgico. Artigos anteriores mostraram que a frequência de SPI em pacientes com enxaqueca é maior do que nos controles. Desenvolvemos um estudo para avaliar comorbidades, medicamentos utilizados e sintomas depressivos em pacientes com migrânea e SPI. MÉTODOS: Foi desenvolvido um estudo de caso-controle. Foram entrevistados pacientes com enxaqueca (n=72) e sujeitos de um grupo controle (n=72). Foram avaliados dados incluindo diagnóstico de SPI, sintomas depressivos, comorbidades e medicamentos usados. RESULTADOS: Houve associação significativa entre enxaqueca e SPI (p=0,01). Comorbidades como diabetes, hipertensão, anemia ou drogas utilizadas não explicam esta associação. Escores de depressão, medidos pelo Inventário de Beck, foram mais altos em pacientes com enxaqueca e SPI (p=0,04). CONCLUSÃO: Não foram encontrados fatores específicos que explicam a associação entre enxaqueca e SPI. Sintomas de depressão foram mais frequentes em pacientes com enxaqueca e SPI.